The effect of caffeine chewing gum on neuromuscular and cardiorespiratory responses after severe intensity exercise in trained cyclists - Nascimento, Eduardo Marcel Fernandes (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2024.